2019
DOI: 10.3847/1538-4357/ab4ad7
|View full text |Cite
|
Sign up to set email alerts
|

Progenitors of Type IIb Supernovae. I. Evolutionary Pathways and Rates

Abstract: Type IIb supernovae (SNe) are important candidates to understand mechanisms that drive the stripping of stripped-envelope (SE) supernova (SN) progenitors. While binary interactions and their high incidence are generally cited to favor them as Type IIb SN progenitors, this idea has not been tested using models covering a broad parameter space. In this paper we use single-and binary-star models at solar and low metallicities covering a broad parameter space to investigate the progenitors of and evolutionary path… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 128 publications
4
59
0
Order By: Relevance
“…WR stars have mass loss rates similar to red supergiants, but with winds speeds two orders of magnitude higher. However, the low mass of the progenitor is incompatible with a WR phase (Sravan et al 2019). In addition, hydrodynamical simulations of van Veelen et al (2009), showed the QSFs cannot be explained by a WR wind and the remnant's emission did not show evidence for remainders of a WR shell.…”
Section: Cas A's Progenitor Mass-loss Historymentioning
confidence: 99%
“…WR stars have mass loss rates similar to red supergiants, but with winds speeds two orders of magnitude higher. However, the low mass of the progenitor is incompatible with a WR phase (Sravan et al 2019). In addition, hydrodynamical simulations of van Veelen et al (2009), showed the QSFs cannot be explained by a WR wind and the remnant's emission did not show evidence for remainders of a WR shell.…”
Section: Cas A's Progenitor Mass-loss Historymentioning
confidence: 99%
“…Comparison of these constraints with the full distribution of theoretical properties not only help ascertain the prevalence of observed properties in nature, but can also reveal currently unobserved populations. In this follow-up paper, we use the large grid of models presented in Sravan et al (2019) to derive distributions of single and binary SNe IIb progenitor properties and compare them to constraints from three independent observational probes: multi-band SN light-curves, direct progenitor detections, and X-ray/radio observations. Consistent with previous work, we find that while current observations exclude single stars as SN IIb progenitors, SN IIb progenitors in binaries can account for them.…”
mentioning
confidence: 99%
“…In particular, our models indicate the existence of a group of highly stripped (envelope mass ∼ 0.1 − 0.2M ) progenitors that are compact (< 50R ) and blue (T eff 10 5 K) with ∼ 10 4.5 − 10 5.5 L and low density circumstellar mediums. As discussed in Sravan et al (2019), this group is necessary to account for SN IIb fractions and likely exist regardless of metallicity. The detection of the unobserved populations indicated by our models would support weak stellar winds and inefficient mass transfer in SN IIb progenitors.…”
mentioning
confidence: 99%
“…Woosley, Heger & Weaver 2002) and the fraction of SNe IIP is higher (e.g. Heger et al 2003;Woosley & Heger 2015;Sravan, Marchant & Kalogera 2019). At increased metallicity, mass-loss reduces the hydrogen envelope and only SNe IIL/IIb result (Heger et al 2003).…”
mentioning
confidence: 99%